Preparation method and application of mixed matrix membrane based on MIL-101-F
By combining MIL-101-F with polyimide, a hybrid matrix membrane with high porosity and stability was prepared, solving the ‘trade-off’ problem between selectivity and permeability of traditional membrane materials in gas separation, achieving efficient carbon dioxide/methane separation performance.
Patent Information
- Application Number
- CN202411967990.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-30
AI Technical Summary
There is a ‘trade-off’ effect between gas selectivity and permeability during the separation process of existing gas separation membrane materials, making it difficult to achieve high stability, high permeability and high selectivity at the same time.
Using a mixed matrix membrane based on MIL-101-F, membrane materials with high porosity, chemical stability and thermal stability were prepared by combining the fluorinated metal-organic framework MIL-101-F with polyimide (6FDA-DAM).
High permeability and high selectivity gas separation performance are achieved, especially in carbon dioxide/methane separation applications, and the preparation method is simple and easy to be used in industrial applications.
Smart Images

Figure CN119733393A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of membrane preparation technology and gas separation, and specifically relates to a preparation method and application of a mixed matrix membrane based on MIL-101-F. Background Art
[0002] After the Industrial Revolution, human activities, fossil fuel combustion, and natural gas exploration have released a large amount of carbon dioxide into the environment, causing the greenhouse effect and global warming. Global warming will bring serious environmental problems, so carbon capture and storage (CCS) is of vital importance to mitigate climate change caused by carbon dioxide emissions.
[0003] The development of efficient carbon dioxide capture and separation technology is of great significance for controlling and reducing global greenhouse gas emissions. At present, the main methods used for gas separation on an industrial scale include separation technologies such as cryogenic distillation, pressure swing adsorption and chemical solvent absorption. However, these traditional separation methods are characterized by high energy consumption, complicated processes and large equipment investment. As a new type of separation technology, membrane separation technology is favored by these traditional separation processes because of its advantages such as low energy consumption, low operating temperature, low initial installation cost, green environmental protection and simple operation. Membrane separation technology does not produce phase changes during the separation process, so it can save more energy. At the same time, the membrane separation process does not require solid or liquid adsorbents that consume energy costs to regenerate. Membrane separation technology has been widely studied and applied to various fields such as industrial production and daily life, and is expected to help achieve the strategic goals of "carbon neutrality and carbon peak".
[0004] Gas separation membrane technology is a separation process driven by pressure difference. The pressure difference between the two sides of the membrane is the driving force. Different types of gases are effectively separated according to their different permeation rates in the gas separation membrane. However, most polymer membranes are prone to aging and there is a "trade-off" effect between gas selectivity and permeability, that is, during the separation process, the gas permeability increases and the selectivity decreases; the gas separation selectivity increases and the gas permeability decreases. Therefore, the development and preparation of a membrane material with high stability, high permeability and high selectivity is the key to achieving efficient membrane separation.
[0005] In order to solve this scientific problem, many researchers have prepared mixed matrix membranes by adding excellent fillers into polymer matrices. Mixed matrix membranes are a new type of separation membrane that integrates organic polymers as continuous phases with dispersed inorganic components, successfully combining the advantages of commercial polymers and designable inorganic fillers. Mixed matrix membranes not only utilize the unique advantages of inorganic fillers in gas adsorption and pore screening, but also retain the good processability and physical durability of polymer materials, and are expected to solve the "trade-off" effect of polymer membranes.
[0006] Mixed matrix membrane (MMM) is a type of membrane that introduces inorganic fillers into a polymer matrix and combines the advantages of both. The most commonly used fillers include silica, zeolite, graphene oxide and metal organic frameworks (MOFs). Typical inorganic materials such as silica and zeolite often cause structural defects in the separation membrane due to their poor interfacial compatibility with polymers, resulting in poor selectivity of gas separation membranes and unfavorable separation processes. The new porous material MOFs improves the compatibility problem with polymers due to the organic part in its structure. At the same time, the biggest feature of MOFs is the adjustability of its material structure, which makes it have "designable" pore size, surface function, physical and chemical properties. MOFs has become a very promising material for the preparation of mixed matrix membranes. At present, MOFs are added as fillers to the polymer matrix, combining the advantages of polymerization and MOFs, and mixed matrix membranes with good separation performance can be prepared. However, when the loading amount of MOF increases, it is very easy to settle and agglomerate in the polymer matrix. The uneven dispersion of the filler limits the improvement of its gas separation performance. It is very challenging to prepare a mixed matrix membrane with high compatibility between fillers and polymer matrices, while reducing interface defects and maintaining the flexibility of the polymer membrane. At present, researchers have made many effective explorations and studies on how to improve the interface compatibility between porous materials MOFs and polymers. These include methods such as regulating particle size, preparing composite materials, and in-situ growth. Due to the easy functionalization of MOFs, the method of changing the surface chemical properties of MOFs through surface modification technology to enhance compatibility with polymers has become a research hotspot. Summary of the invention
[0007] In view of the problems existing in the prior art, the present invention provides a preparation method and application of a mixed matrix membrane based on MIL-101-F. The mixed matrix membrane based on MIL-101-F can be used for separation of carbon dioxide / methane.
[0008] The present invention is achieved through the following technical solutions: A mixed matrix membrane based on MIL-101-F, wherein the dispersed phase of the mixed matrix membrane is fluorinated metal-organic framework MIL-101-F, and the continuous phase of the mixed matrix membrane is polyimide 6FDA-DAM.
[0009] Furthermore, the filling amount of the fluorinated metal-organic framework MIL-101-F in the mixed matrix membrane is 5-25wt%.
[0010] Furthermore, the filling amount of the fluorinated metal-organic framework MIL-101-F in the mixed matrix membrane is 10 wt %.
[0011] Furthermore, the preparation method of MIL-101-F includes the following steps: adding 125 mg of chromium trioxide and 225 mg of 2-fluoroterephthalic acid (H2BDC-F) to 5 mL of deionized water, magnetically stirring for 30 minutes, adding 0.1 mL of HCl after mixing evenly, sealing and performing a solvent thermal reaction at 453 K, and collecting a green powdery crude product by centrifugation after the reaction is completed, and then washing it three times with deionized water, hot DMF and ethanol respectively, and drying the obtained green powder in a vacuum oven at 150°C for 6 hours.
[0012] Furthermore, the preparation method of the polyimide (6FDA-DAM) comprises the following steps: S1. Place the cleaned three-necked flask in a 120°C oven and dry for 10 h, then purge with dry nitrogen for 20 min; S2, add (14.33mmol) DAM to a three-necked flask, add 15mL NMP to completely dissolve DAM; cool the three-necked flask to 0°C in an ice bath, slowly add 6.364g (14.33mmol) 4,4'-(hexafluoroisopropylene) diphthalic anhydride 6FDA into the mixed solution in three equal portions, and finally add another 15mL NMP; mechanically stir for 24h under a nitrogen atmosphere to form a viscous polyamic acid; S3. After 24 hours, remove the ice bath, add 2 mL of activator triethylamine and 5.4 mL of dehydrating agent acetic anhydride, immediately dilute the viscous solution with 6 mL of NMP, and mechanically stir for 24 hours to form polyimide by imidization. After the imidization is completed, pour the viscous polyimide solution into 500 mL of methanol for precipitation, rinse the polyimide with methanol, place it in a new batch of methanol, repeat the process 3 times, and then put it into a vacuum drying oven at 180°C for 24 hours.
[0013] The present invention also provides a method for preparing the mixed matrix membrane based on MIL-101-F, comprising the following steps: S1, dispersing the fluorinated metal-organic framework MIL-101-F prepared in Example 1 into an organic solvent, stirring, and ultrasonicating for 30 min-1 h to obtain a MIL-101-F suspension; S2, adding polyimide (6FDA-DAM) to the MIL-101-F suspension, stirring for 12 hours, and ultrasonicating to obtain a mixed matrix membrane film-forming solution; S3, the mixed matrix membrane film-forming solution obtained in step S2 was poured into a 46 × 18mm flat glass film-forming surface dish, and then the surface dish was placed in a constant temperature and humidity chamber for 24-48h to completely evaporate the solvent; S4. The membrane was then placed in a vacuum oven and degassed and dried at 120° C. for 24 hours to obtain a mixed matrix membrane based on MIL-101-F.
[0014] Furthermore, the drying temperature during the evaporation of the solvent was 26.5° C. and the drying humidity was 35%.
[0015] Furthermore, the organic solvent is chloroform, which has a low boiling point, is easily volatile, and has a high solubility in polyimide.
[0016] The present invention also provides the use of the mixed matrix membrane based on MIL-101-F in separating CO2 / CH4.
[0017] Beneficial technical effects of the present invention: The present invention uses the metal-organic framework material MIL-101-F with high porosity, chemical stability and thermal stability, cheap raw materials and simple synthesis process as the dispersed phase, and the high molecular weight polyimide (6FDA-DAM) with high gas permeability and separation selectivity as the continuous phase. By strictly controlling the volatilization temperature and humidity of the membrane-building liquid, a metal-organic framework mixed matrix membrane is prepared, and a high permeability and high selectivity mixed matrix membrane for carbon dioxide / methane separation is obtained, which is used to separate CO2 and CH4 in industrial scenarios. The preparation method of the mixed matrix membrane in the present invention is simple, easy to implement, and easy to mass produce, with high CO2 / CH4 separation performance, and the metal-organic framework MIL-1010-F has a low doping amount, which is easy to industrialize. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The SEM images of MIL-101 and MIL-101-F samples; Figure 2 This is the energy dispersive X-ray spectrum (EDX) of MIL-101-F; Figure 3 The X-ray powder diffraction (PXRD) patterns of MIL-101 and its modified derivative MIL-101-F; Figure 4 The mixed matrix membranes obtained in Examples 3-7 and Comparative Example 1 were subjected to X-ray powder diffraction (PXRD) patterns; Figure 5 Fourier transform infrared spectroscopy (FTIR) characterization diagram of the mixed matrix membrane obtained in Examples 3-5, 7 and Comparative Example 2; Figure 6 Differential scanning calorimetry images of mixed matrix membranes with different loading amounts of MIL-101-F and original 6FDA-DAM membrane; Figure 7 Thermogravimetric analysis of mixed matrix membranes with different loading amounts of MIL-101-F and original 6FDA-DAM membranes; Figure 8SEM images of mixed matrix membranes with different loading amounts of MIL-101-F; Fig. 9 Energy dispersive X-ray spectra of mixed matrix membranes with different loading amounts of MIL-101-F; Fig.10 (a) Hardness variation of MIL-101-F-10% mixed matrix film and original 6FDA-DAM film with displacement: (b) Modulus variation of MIL-101-F-10% mixed matrix film and original 6FDA-DAM film with displacement: Fig.11 The separation performance diagram of mixed matrix membranes with different loading amounts of MIL-101-F; Fig.12 The separation performance diagram of mixed matrix membranes with different loading amounts of MIL-101; Fig.13 The single component gas permeation test results of MIL-101-F-10% mixed matrix membrane and original 6FDA-DAM membrane at different pressures are shown in the figure; Fig.14 This is the result of binary CO2 / CH4 (50:50) gas permeation test of MIL-101-F at different pressures; Fig.15 Graph showing the CO2 / CH4 separation performance of polyimide-based mixed matrix membranes prepared using different fillers (such as MOCs, MOFs and COFs) in the prior art.
[0020] Fig.16 (a) Single-component adsorption isotherms of MIL-101-F and (b) 6FDA-DAM membranes for CO2 and CH4 at 308K; (c) Solubility and diffusion coefficient of MIL-101-F and 6FDA-DAM membranes; (d) Adsorption selectivity and diffusion selectivity of MIL-101-F and 6FDA-DAM membranes for CO2 and CH4 at 308K. DETAILED DESCRIPTION
[0021] Example 1 Preparation of MIL-101-F 125 mg of chromium trioxide and 225 mg of 2-fluoroterephthalic acid (H2BDC-F) were added to 5 mL of deionized water and stirred magnetically for 30 minutes. After mixing evenly, 0.1 mL of HCl was added. The mixture was sealed and subjected to solvent thermal reaction at 453 K. After the reaction was completed, the crude green powder was collected by centrifugation and then washed three times with deionized water, hot DMF and ethanol respectively. The obtained green powder was dried in a vacuum oven at 150 °C for 6 hours.
[0022] Preparation of MIL-101 125 mg of chromium trioxide and 225 mg of terephthalic acid (H2BDC) were added to 5 mL of deionized water and stirred magnetically for 30 minutes. After mixing evenly, 0.1 mL of HCl was added. The mixture was sealed and subjected to solvent thermal reaction at 453 K. After the reaction was completed, a green powdery crude product was collected by centrifugation and then washed three times with deionized water, hot DMF and ethanol respectively. The obtained green powder was dried in a vacuum oven at 150 °C for 6 hours.
[0023] The MIL-101-F and MIL-101 obtained in Example 1 were characterized: The morphology and structural properties of MIL-101 and MIL-101-F samples were analyzed and compared in detail. Scanning electron microscope (SEM) images ( Figure 1 ) showed that the particle size of MIL-101 was about 300 nm, while that of MIL-101-F was reduced to about 100 nm, both of which maintained an octahedral crystal structure. Comparative analysis showed that the particle size of MIL-101-F was significantly reduced. This phenomenon was attributed to the introduction of substituents of different sizes, which increased the steric hindrance effect. The enhanced steric hindrance inhibited crystallization by hindering the nucleation and subsequent lattice growth process. Therefore, the size-reduced MIL-101-F had higher filler dispersibility in the solvent and showed better compatibility with the polymer matrix.
[0024] The synthesis of the MIL-101-F metal organic framework (MOF) was successfully verified by energy dispersive X-ray spectroscopy (EDX) analysis. The presence of fluorine was detected, indicating that the F element had been successfully incorporated into the lattice of MIL-101-F (e.g. Figure 2 as shown).
[0025] Figure 3 The X-ray powder diffraction (PXRD) patterns of MIL-101 and its modified derivative MIL-101-F are shown. A clear diffraction peak was observed at about 2θ=3.3°. The experimental PXRD patterns of MIL-101 and MIL-101-F are highly consistent with the simulation results. This indicates that MIL-101-F has the same crystal structure as MIL-101.
[0026] Example 2 Preparation of polyimide (6FDA-DAM) S1. Place the cleaned three-necked flask in a 120°C oven and dry for 10 h, then purge with dry nitrogen for 20 min; S2, add (14.33mmol) DAM to a three-necked flask, add 15mL NMP to completely dissolve DAM; cool the three-necked flask to 0°C in an ice bath, slowly add 6.364g (14.33mmol) 4,4'-(hexafluoroisopropylene) diphthalic anhydride 6FDA into the mixed solution in three equal portions, and finally add another 15mL NMP; mechanically stir for 24h under a nitrogen atmosphere to form a viscous polyamic acid; S3. After 24 hours, remove the ice bath, add 2 mL of activator triethylamine and 5.4 mL of dehydrating agent acetic anhydride, immediately dilute the viscous solution with 6 mL of NMP, and mechanically stir for 24 hours to form polyimide by imidization. After the imidization is completed, pour the viscous polyimide solution into 500 mL of methanol for precipitation, rinse the polyimide with methanol, place it in a new batch of methanol, repeat the process 3 times, and then put it into a vacuum drying oven at 180°C for 24 hours.
[0027] Example 3 Mixed matrix membrane with 5 wt% MIL-101-F loading Disperse 3.16 mg of the fluorinated metal-organic framework MIL-101-F prepared in Example 1 into 5 ml of chloroform, stir, and ultrasonicate for 30 min-1 h to obtain a MIL-101-F suspension; 60 mg of polyimide (6FDA-DAM) was added to the MIL-101-F suspension, stirred for 12 h, and ultrasonicated to promote the complete dissolution of the polymer to obtain a mixed matrix membrane film-forming solution; Pour the membrane-building solution into a flat-bottomed glass culture dish, cover it with a polyethylene (PE) sealed bag, and then place the surface dish in a constant temperature and humidity chamber to evaporate for 24-48 hours to completely evaporate the solvent. The drying temperature during solvent evaporation is 26.5°C and the drying humidity is 35%; Deionized water was added to the petri dish, and the membrane was gently removed with tweezers. The membrane was then placed in a vacuum oven and degassed and dried at 120°C for 24 hours to obtain a mixed matrix membrane based on MIL-101-F.
[0028] Example 4 Mixed matrix membrane with 10 wt% MIL-101-F loading The difference between Example 4 and Example 3 is that the added amount of the fluorinated metal-organic framework MIL-101-F is 6.67 mg, and the other conditions are exactly the same.
[0029] Example 5 Mixed matrix membrane with 15 wt% MIL-101-F loading The difference between Example 5 and Example 3 is that the added amount of the fluorinated metal-organic framework MIL-101-F is 10.59 mg, and the other conditions are exactly the same.
[0030] Example 6 Mixed matrix membrane with 20 wt% MIL-101-F loading The difference between Example 6 and Example 3 is that the added amount of the fluorinated metal-organic framework MIL-101-F is 15 mg, and the other conditions are exactly the same.
[0031] Example 7 Mixed Matrix Membrane with 25 wt% MIL-101-F Loading The difference between Example 7 and Example 3 is that the added amount of the fluorinated metal-organic framework MIL-101-F is 20 mg, and the other conditions are exactly the same.
[0032] Comparative Example 1 Mixed Matrix Membrane with 30 wt% MIL-101-F Loading The difference between the comparative example and Example 3 is that the added amount of the fluorinated metal-organic framework MIL-101-F is 28.71 mg, and the other conditions are exactly the same.
[0033] Comparative Example 2 Pure 6FDA-DAM membrane The difference between Comparative Example 2 and Example 3 is that the added amount of the fluorinated metal-organic framework MIL-101-F is 0 mg, and the other conditions are exactly the same.
[0034] Comparative Example 3 Mixed Matrix Membrane with 10 wt% MIL-101 Loading The difference between Comparative Example 3 and Example 4 is that the fluorinated metal-organic framework is MIL-101, the addition amount is 6.67 mg, and the other conditions are exactly the same.
[0035] The mixed matrix membranes obtained in Examples 3-7 were characterized by X-ray powder diffraction (PXRD). Figure 4 , it can be seen that as the amount of MIL-101-F increases, the intensity of the corresponding diffraction peak also increases, which indicates that MIL-101-F maintains the integrity of the crystal in the mixed matrix membrane. The crystal structure does not undergo characteristic peak shifts, indicating that the MIL-101-F crystals are not structurally damaged during the formation of the mixed matrix membrane. The retention of this structure enables the pores within the MIL-101-F framework to be used for gas molecule transport. However, when the amount of MIL-101-F added is further increased, the structure of the mixed matrix membrane cannot be maintained because the MOF filler aggregates in the membrane, resulting in uneven dispersion in the polymer matrix, which affects the formation of the membrane structure.
[0036] In order to study the chemical interaction between MIL-101-F filler and polymer matrix, the mixed matrix membranes obtained in Examples 3, 4, 5, 7 and Comparative Example 2 were characterized by Fourier transform infrared spectroscopy (FTIR). Figure 5In the MIL-101-F / 6FDA-DAM mixed matrix membrane, no new absorption peaks appeared, indicating that no chemical reaction occurred between the MIL-101-F crystals and the 6FDA-DAM polymer chains during the membrane preparation process. However, with the addition of a small amount of MIL-101-F, the -NH- vibration peak of 6FDA-DAM (originally located at about 1627cm⁻¹) in the composite matrix membrane prepared in Example 3 showed a weak blue shift to 1624cm⁻¹. In addition, with the increase of filler concentration, the -NH peaks in the composite matrix membranes prepared in Examples 5 and 7 further blue shifted, and were located at 1621cm⁻¹ and 1619cm⁻¹, respectively. The above phenomena indicate that there is a weak intermolecular force between the MIL-101-F metal organic framework and the polyimide chain, which may affect the dispersibility of the filler in the matrix and the arrangement of the polymer segments.
[0037] In order to further study the interaction between MIL-101-F filler and polymer in the mixed matrix membrane, the differential scanning calorimetry (DSC) of the membranes prepared in Examples 3, 4 and Comparative Example 2 was measured using a synchronous thermal analyzer (TG-DSC). Figure 6 , and thermogravimetric analysis (TG) of the films prepared in Examples 3, 4, 7 and Comparative Example 2, the results are shown in Figure 7 , the change in glass transition temperature (Tg) is an indication of the interaction between the filler and the polymer matrix. During the membrane preparation process, when the polymer and filler are mixed to form a membrane by solvent evaporation, covalent bonds are usually not formed. However, the polar groups of the filler may have intermolecular interactions (such as hydrogen bonding, van der Waals forces, etc.) with the chain segments of the polar polymer. Figure 6 As shown in the figure, compared with the 6FDA-DAM membrane prepared in Comparative Example 2, the Tg of the membrane of Example 4 is significantly increased from 367°C to 383°C. This increase is due to the presence of a large number of polar functional groups (-F) in MIL-101-F, which hinder the movement of the polymer chain and the molecular interaction between the MIL-101-F framework and 6FDA-DAM. Thermogravimetric analysis curve of the mixed matrix membrane ( Figure 7 ) showed that the introduction of MIL-101-F fillers did not reduce the stability of the membranes, indicating that they still had good thermal stability.
[0038] The poor aggregation and dispersion of the inorganic filler MIL-101-F is one of the main challenges in the preparation of mixed matrix membranes. By introducing hydrophobic functional groups to modify the pore environment, it is expected that the organic component in the ligand can improve the compatibility with the polymer, thereby enhancing the dispersibility of the filler. In the present invention, the MOF filler MIL-101-F exhibits good dispersibility in chloroform, allowing it to be uniformly mixed with the polymer 6FDA-DAM in the casting solvent, thereby solving the problem of filler aggregation during membrane preparation. The micromorphology and structure of pure membranes and mixed matrix membranes with different loading amounts of MIL-101-F / 6FDA-DAM were observed using a scanning electron microscope (SEM). Figure 8 As shown in Figure 2, the SEM images of the membrane surface show that the distribution of MOF particles on the surface of the mixed matrix membrane increases significantly with the increase of the MOF filler content, but remains relatively uniform. In the cross-sectional view, when the filler loading is less than 20%, the MOF particles are dispersed in the pores of the polymer, and no obvious deposition or aggregation is observed, indicating that MIL-101-F has good interfacial compatibility with the polymer 6FDA-DAM and achieves good dispersion in the membrane. Energy dispersive X-ray spectroscopy (EDX) analysis can intuitively observe the element content and distribution on the surface and in the cross section of the MIL-101-F-10% membrane. Figure 8 and Fig. 9 The results show that C, N, O, F and Cr elements are evenly distributed on the surface and cross-section of the membrane. Because Cr, as a characteristic element of MIL-101-F, only exists in the filler, and the polymer 6FDA-DAM does not contain this element. Therefore, the distribution of Cr, the characteristic element of MIL-101-F, can reflect the dispersion effect of MOF filler. EDX spectral data proves that MIL-101-F has good dispersibility in the mixed matrix membrane of Example 4, and the filler is evenly distributed in the polymer matrix. The good dispersibility and compatibility of MIL-101-F filler and 6FDA-DAM polymer can avoid performance degradation caused by filler aggregation. This uniform distribution improves the gas separation performance and mechanical stability of the membrane.
[0039] The mechanical properties of the mixed matrix membranes prepared in Example 4 and Comparative Example 2 were studied at the nanoscale using the continuous stiffness measurement (CSM) technique. The CSM technique vibrates the indentation probe and measures the mechanical properties of the material such as modulus, hardness and contact stiffness through a signal amplifier at a specific frequency. Fig.10As shown, in the range of 400-800nm, the hardness and modulus obtained from the load-displacement curve of the MIL-101-F-10% mixed matrix membrane are significantly higher than those of the pure 6FDA-DAM membrane. The test data show that the average modulus of the MIL-101-F-10% mixed matrix membrane and the pure 6FDA-DAM membrane are 2.9GPa and 2.6GPa, respectively, while the average hardness is 0.21GPa and 0.19GPa, respectively. This indicates that the mechanical properties of the MIL-101-F-10% mixed matrix membrane are better than those of the pure 6FDA-DAM membrane.
[0040] Gas separation performance testing of mixed matrix membranes (1) Single-component gas permeability Fig.11 and Fig.12 The figure shows the separation performance of mixed matrix membranes with different loading amounts of MIL-101-F and MIL-101. The results show that compared with the unfilled 6FDA-DAM membrane, the mixed matrix membrane of MIL-101-F and MIL-10 significantly improves the CO2 permeability, which is attributed to the interaction between MIL-101, MIL-101-F and CO2, and the pore structure of the filler provides additional mass transfer channels for CO2.
[0041] The CO2 permeability of the mixed matrix membrane prepared in Example 4 is 2.5 times that of the pure 6FDA-DAM membrane, while the selectivity remains basically unchanged. In contrast, the CO2 permeability of the mixed matrix membrane prepared in Comparative Example 3 is only 1.5 times that of the pure 6FDA-DAM membrane, and the selectivity drops to about 15.
[0042] As the filling amount of MIL-101-F increases, the CO2 permeability of the mixed matrix membrane continues to increase. When the filling amount of MIL-101-F reaches 10%, the CO2 permeability is about 3500 Barrer, which is almost 2.5 times that of the pure membrane. However, when the filling amount is further increased (from 10% to 25%), the separation selectivity of CO2 / CH4 decreases with the increase of the filling amount. Overall, the MIL-101-F-10% membrane exhibits the most superior separation performance.
[0043] (2) Effect of operating pressure on membrane separation performance Single component gas permeation tests were performed on MIL-101-F-10% mixed matrix membranes at pressures ranging from 3 to 9 bar and temperatures of 35°C (see Table 1). Fig.13As shown). As the feed pressure increases from 3 bar to 9 bar, the CO2 permeability and CO2 / CH4 selectivity of the MIL-101-F-10% membrane decrease. The CO2 permeability decreases from 3500 Barrer to 2672 Barrer, while the CO2 / CH4 selectivity decreases from 18 to 16.4. In order to compare the performance with that of the pure 6FDA-DAM membrane, a single-component gas permeation experiment was also carried out on the pure 6FDA-DAM membrane under the same conditions. As the pressure increases, the CO2 permeability of the pure membrane decreases from 1400 Barrer to 1051 Barrer, while the CO2 / CH4 selectivity decreases from 17.2 to 15.7. Obviously, at all test pressures, the separation performance of the MIL-101-F-10% membrane is better than that of the pure 6FDA-DAM membrane, see Fig.13 .
[0044] Subsequently, binary gas permeation experiments were carried out on MIL-101-F-10% mixed matrix membrane and 6FDA-DAM membrane using CO2 / CH4 (50:50, v / v) mixed gas under the same operating conditions (3-9 bar, 35 °C) (e.g. Fig.14 ). With the increase of test pressure, the CO2 permeability of MIL-101-F-10% mixed matrix membrane only slightly decreased from 1686 Barrer to 1391 Barrer, and the decrease of CO2 / CH4 selectivity was also extremely limited. In contrast, the CO2 permeability of pure 6FDA-DAM membrane decreased from 689 Barrer to 523 Barrer, and the CO2 / CH4 selectivity decreased from 17.2 to 13.2. Therefore, compared with pure 6FDA-DAM membrane, MIL-101-F-10% mixed matrix membrane effectively alleviated the plasticization effect under high pressure, which may be due to the interaction between polymer chains and MIL-101-F, which reduced the mobility of polymer chain segments.
[0045] Fig.15 The CO2 / CH4 separation performance of polyimide-based mixed matrix membranes prepared with different fillers (such as MOCs, MOFs and COFs) in the prior art is summarized. As can be seen from the figure, the gas separation performance of the mixed matrix membrane filled with MIL-101-F-10% exceeds the separation upper limit proposed by Robeson in 2008. Compared with the polyimide-based mixed matrix membranes reported in recent years, the MIL-101-F-10% membrane shows better performance in CO2 / CH4 separation.
[0046] (3) Gas separation mechanism of MIL-101-F / 6FDA-DAM mixed matrix membrane (MMM) CO2 and CH4 gas adsorption isotherms based on pure 6FDA-DAM membrane and MIL-101-F-10% mixed matrix membrane ( Fig.16 ), the solubility coefficients and diffusion coefficients of CO2 and CH4 were calculated using the dual-site adsorption model. As shown in Figure 17, the solubility coefficients of CO2 and CH4 in the MIL-101-F-10% mixed matrix membrane are higher than those in the pure 6FDA-DAM membrane, which is consistent with the single-component gas adsorption isotherm results of the membrane. Due to the presence of MIL-101-F, the CO2 diffusion coefficient in the MIL-101-F-10% mixed matrix membrane increased from 15.3 (10 -7 cm 2 s -1 ) increased to 30.5 (10 -7 cm 2 s -1 ), the CH4 diffusion coefficient increases from 3.7 (10 -7 cm 2 s -1 ) increased to 6.1 (10 - 7 cm 2 s -1 ). This indicates that the main role of MIL-101-F-10% in the membrane is to enhance the diffusion coefficient, which is a key factor in the increase in CO2 permeability. In addition, the adsorption selectivity of the original 6FDA-DAM membrane is 4.45, which is higher than the value of the MIL-101-F-10% mixed matrix membrane, while the diffusion selectivity increases significantly, from 4.09 to 5.06. Therefore, the significant improvement in the CO2 / CH4 separation performance in the MIL-101-F-10% mixed matrix membrane can be attributed to the increase in CO2 diffusion rate. In summary, the fluorinated modifier in the filler MIL-101-F provides additional CO2 transmission channels for the mixed matrix membrane, helps to improve the CO2 permeability and selectivity, and plays an important role in the prepared mixed matrix membrane.
Claims
1. A mixed matrix membrane based on MIL-101-F, characterized in that: The dispersed phase of the mixed matrix membrane is a fluorinated metal-organic framework MIL-101-F, and the continuous phase of the mixed matrix membrane is a polyimide 6FDA-DAM.
2. The mixed matrix membrane based on MIL-101-F according to claim 1, characterized in that: The filling amount of MIL-101-F is 5-25wt%.
3. The mixed matrix membrane based on MIL-101-F according to claim 2, characterized in that: The filling amount of the fluorinated metal-organic framework MIL-101-F in the mixed matrix membrane is 10 wt %.
4. The mixed matrix membrane based on MIL-101-F according to claim 1, characterized in that: The preparation method of MIL-101-F comprises the following steps: adding 125 mg of chromium trioxide and 225 mg of 2-fluoroterephthalic acid (H2BDC-F) into 5 mL of deionized water, stirring magnetically for 30 minutes, adding 0.1 mL of HCl after mixing evenly, sealing and performing a solvent thermal reaction at 453 K, collecting a green powdery crude product by centrifugation after the reaction is completed, then washing three times with deionized water, hot DMF and ethanol respectively, and drying the obtained green powder in a vacuum oven at 150° C. for 6 hours.
5. The mixed matrix membrane based on MIL-101-F according to claim 1, characterized in that: The polyimide (6FDA-DAM) preparation method comprises the following steps: S1. Place the cleaned three-necked flask in a 120°C oven and dry for 10 h, then purge with dry nitrogen for 20 min; S2, add (14.33mmol) DAM to a three-necked flask, add 15mL NMP to completely dissolve DAM; cool the three-necked flask to 0°C in an ice bath, slowly add 6.364g (14.33mmol) 4,4'-(hexafluoroisopropylene) diphthalic anhydride 6FDA into the mixed solution in three equal portions, and finally add another 15mL NMP; mechanically stir for 24h under a nitrogen atmosphere to form a viscous polyamic acid; S3. After 24 hours, remove the ice bath, add 2 mL of activator triethylamine and 5.4 mL of dehydrating agent acetic anhydride, immediately dilute the viscous solution with 6 mL of NMP, and mechanically stir for 24 hours to form polyimide by imidization. After the imidization is completed, pour the viscous polyimide solution into 500 mL of methanol for precipitation, rinse the polyimide with methanol, place it in a new batch of methanol, repeat the process 3 times, and then put it into a vacuum drying oven at 180°C for 24 hours.
6. A method for preparing a mixed matrix membrane based on MIL-101-F as claimed in any one of claims 1 to 5, characterized in that: The following steps are involved: S1, dispersing the fluorinated metal-organic framework MIL-101-F prepared in Example 1 into an organic solvent, stirring, and ultrasonicating for 30 min-1 h to obtain a MIL-101-F suspension; S2, adding polyimide (6FDA-DAM) to the MIL-101-F suspension, stirring for 12 hours, and ultrasonicating to obtain a mixed matrix membrane film-forming solution; S3, the mixed matrix membrane film-forming solution obtained in step S2 was poured into a 46 × 18mm flat glass film-forming surface dish, and then the surface dish was placed in a constant temperature and humidity chamber for 24-48h to completely evaporate the solvent; S4. The membrane was then placed in a vacuum oven and degassed and dried at 120° C. for 24 hours to obtain a mixed matrix membrane based on MIL-101-F.
7. The method for preparing a mixed matrix membrane based on MIL-101-F according to claim 6, characterized in that: The drying temperature when the solvent evaporates is 26.5°C and the drying humidity is 35%.
8. The method for preparing a mixed matrix membrane based on MIL-101-F according to claim 6, characterized in that: The organic solvent is chloroform.
9. Use of the mixed matrix membrane based on MIL-101-F as claimed in any one of claims 1 to 5 in separation of CO2 / CH4.
Citation Information
Patent Citations
Hollow fiber gas separation membrane and preparation method thereof
CN106237862A
Preparation method of polyimide P84 / MIL-101 (Cr) mixed matrix membrane
CN113600038A
Mixed matrix membrane for carbon dioxide / nitrogen separation and preparation method and application thereof
CN116036885A
Preparation method for recovering hydrophobic functional composite membrane in phenol through enhanced pervaporation
CN117563435A